Going Dutch: The management of monetary policy in the Netherlands during the interwar gold standard - Christopher L. Colvin; Philip Fliers (Queen's University Centre for Economic History (QUCEH), 2019)
Under what conditions can policymakers make demonstrably poor policy choices? By providing a new account of monetary policy management in the Netherlands during the interwar gold standard, we show how policymakers can fail to escape their long-held beliefs and refuse to consider available policy alternatives. Using high-frequency macroeconomic data, we are the first to document that the Netherlands' policymakers were able to conduct an independent monetary policy in the 1930s. We then show how this independence was squandered on fixing the guilder's exchange rate, a policy which led only to deflation, trade deficits, corporate bankruptcies and mass unemployment. We explain the government's policy stance by documenting the beliefs of politicians and central bankers, and then by investigating how business leaders and public intellectuals attempted to influence these beliefs.
Keywords: N14; E42; E52; E58; 330; monetary policy; exchange rate policy; gold standard; interwar period; the Netherlands